The Environmental Impact of Sustainable Production and Spending: Evidence from Saudi Companies - Zehri, Chokri (International Journal of Energy Economics and Policy, 2025)
We examine how corporate renewable energy strategies under Saudi Arabia’s Vision 2030 influence environmental sustainability, addressing gaps in understanding decarbonization pathways in fossil fuel-dependent economies. Using a generalized method of moments (GMM) panel regressions and bivariate vector autoregression (BIVAR) models, the analysis evaluates data from 113 Saudi firms (2010-2024) to assess the impact of renewable investments and consumption on greenhouse gas emissions and water stewardship. Results reveal that renewable energy adoption significantly reduces emissions and water management challenges, with policy frameworks like subsidies and regulatory mandates amplifying these benefits. Notably, oil- sector firms demonstrate unique capacities to leverage economies of scale for renewable deployment, while oil price fluctuations create dual pressures on non-oil sectors. The study contributes practical insights for policymakers, emphasizing integrated strategies that combine regulatory coherence, subsidy reallocation, and oil-sector engagement to balance economic diversification with environmental goals.